Delivering integrated policy and services for children - Langford, S. (Statistical and Social Inquiry Society of Ireland, 2007)
The Irish Public Service has been relatively strong historically in the area of policy formulation. I have come to the conclusion, however, that we are relatively weak when it comes to implementation and many good policies fail due to a lack of appropriate structures and processes to ensure their successful implementation from policy objectives to tangible outcomes. This paper outlines the role of the Office of the Minister for Children (OMC), which is seeking to overcome that difficulty and bring about more effective implementation of services and interventions for children through cross-Departmental and cross?sectoral working.
Annual Symposium - Delivering integrated policy and services for children
Read before the Society, 21 June 2007
Keywords: Children; Child policy; Office of the Minister for Children; 314.15